A prospective comparative study of oral and vaginal misoprostol after pre-treatment with single dose of mifepristone for second trimester abortion - Bhaskar, Aastha; Kaushik, Richa; Kumar, Ashwani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Misoprostol is a synthetic PGE1 analogue which induces cervical ripening as well as strong uterine contractions and leads to expulsion of pregnancy. Misoprostol has been shown to have several advantages over other prostaglandins; it is cheap, stable at room temperature and can be given by various routes. Administration of mifepristone 24 to 48 hours before misoprostol decreases mean induction time which varies with route of administration of misoprostol. Methods: 50 women with single intrauterine pregnancy with gestational age 13-20 weeks, admitted in labour room of Obstetrics and Gynaecology, Pt. B.D. Sharma PGIMS, Rohtak for termination of pregnancy (on account of missed abortion, absent liquor or gross congenital malformation) were given 200 mg of mifepristone orally after taking written informed consent and excluding scarred uterus, placenta praevia, bronchial asthma, any cardiovascular disease, clotting disorder, long term use of glucocorticoids and history of glaucoma. Then they were randomized into two groups of 25 women each. Group I included 25 women who received oral misoprostol and group II included 25 women who received vaginal misoprostol. Complete abortion was defined as successful expulsion of both foetus and placenta without any intervention. Failure was defined as cases with incomplete expulsion or incomplete dilatation or no dilatation. Results: The mean number of doses of misoprostol used in groups I and group II were 2.80±1.19 and 2.20±0.86 respectively and the difference was statistically significant (p value 0.04). Out of 25 patients included in each group, 64% (n=16) in group I and 80% (n=20) in group II patients had complete expulsion with misoprostol and remaining 36% (n=9) in group I and 20% (n=5) in group II either needed syntocinon or post expulsion evacuation for retained product of conceptions and who did not respond to the given doses of misoprostol at all required mechanical dilatation and evacuation. But this difference was not statistically significant. The mean induction abortion interval in cases of complete expulsion observed in group I was 10.74±4.12 hours and 8.67±3.23 hours in group II which was statistically significant (p value 0.05). Conclusions: Vaginal route is better than oral route for second trimester termination of pregnancy as it requires less number of Misoprostol doses and shorter induction abortion interval.